Interleukin‐1β exacerbates disease and is a potential therapeutic target to reduce pulmonary inflammation during severe influenza A virus infection. Issue 7 (20th May 2021) - Bawazeer, Abdulah OS; Rosli, Sarah; Harpur, Christopher M; Docherty, Callum AH; Mansell, Ashley; Tate, Michelle D
Abstract: Hyperinflammatory responses including the production of NLRP3‐dependent interleukin (IL)‐1β is a characteristic feature of severe and fatal influenza A virus (IAV) infections. The NLRP3 inflammasome has been shown to play a temporal role during severe IAV immune responses, with early protective and later detrimental responses. However, the specific contribution of IL‐1β in modulating IAV disease in vivo is currently not well defined. Here, we identified that activation of NLRP3‐dependent IL‐1β responses occurs rapidly following HKx31 H3N2 infection, prior to the onset of severe IAV disease. Mature IL‐1β was detectable in vivo in both hemopoietic and nonhemopoietic cells. Significantly, therapeutic inhibition of IL‐1β in the airways with intranasal anti‐IL‐1β antibody treatment from day 3 postinfection, corresponding to the onset of clinical signs of disease, significantly prolonged survival and reduced inflammation in the airways. Importantly, early targeting of IL‐1β from day 1 postinfection also improved survival. Together, these studies specifically define a role for IL‐1β in contributing to the development of hyperinflammation and disease and indicate that targeting IL‐1β is a potential therapeutic strategy for severe IAV infections. Abstract : There is an urgent need to develop new drugs that limit damaging inflammation during severe influenza virus infection. Here, we illustrate that interleukin‐1β responses are rapidly activated in the lung during severe influenza virus infection, promoting hyperinflammation and disease development. Our data highlight the therapeutic potential and efficacy of targeting interleukin‐1β to limit severe influenza A virus infection.